Optimization strategy of virtual machine online migration with awareness of application characteristics and network bandwidth migration - Xiang LI; Ning-jiang CHEN; Shang-lin YANG; Hua LI (Tongxin xuebao)
Firstly the experiments to verify the relationship between the number of dirty memory pages and application characteristics which exist in virtual machine migration was conducted.Then,different virtual machine application characteristics were perceived,with which the number of dirty memory pages produced during the migrations was predicted by the use of GM(1,N) grey prediction model.At the same time,using residual correction to adjust error makes results more reliable.According to the prediction of memory dirty pages,network bandwidth was adjusted and reserved.Compared with the traditional pre-copy strategy,the given experiments show that the optimized strategy proposed can improve the performance of network and reduce migratory cost for the memory-intensive and network-intensive applications.